The management features of project initiation under safety management system - Москалюк, Андрей Юрьевич; Тесленко, Павел Александрович; Федунец, Петр Дмитриевич (Eastern-European Journal of Enterprise Technologies, 2012)
The model of project management systems and safety management system of a company is considered. It was shown that the activities for labor protection have the properties of the projects. The procedures of project initiation and activities providing labour protection are presented